From Technical Aid to Strategic Leverage: Taiwan’s Agricultural Diplomacy in Indonesia’s Food Security Sector - Wattimena, Tiara Cornelia (Jurnal Transformasi Global, 2025)
This paper explored that despite the absence of formal diplomatic relations between Indonesia and Taiwan, Taiwan has effectively practised pragmatic diplomacy—a practical, flexible, and results-orientated approach—in the case of agricultural cooperation. This paper examines the case of Taiwan's agricultural mission in Indonesia and explores how a technical collaboration through development cooperation under foreign policies can transform an aid programme into a food security interest in developing nations. In case study ICDF TTM Indonesia, this paper found that the pragmatic diplomacy concept can shift a technical role into high-level diplomatic engagement, both vertically and horizontally. Involving interview with Taiwan’s agriculture representative in Indonesia, this paper found the consistency of bottom-up diplomacy approach by small states that have limited restrictions can have significant engagement, and adding more confidence to perform top-down diplomacy with higher level of actors and audience. This paper conclude that Taiwan’s pragmatic diplomacy and its approaches succeed to make diplomatic level engaments.